A Solution‐Processed Hole Extraction Layer Made from Ultrathin MoS2 Nanosheets for Efficient Organic Solar Cells. Issue 10 (24th July 2013) - Gu, Xing; Cui, Wei; Li, Hai; Wu, Zhongwei; Zeng, Zhiyuan; Lee, Shuit‐Tong; Zhang, Hua; Sun, Baoquan
<x xml:space="preserve">Abstract</x> Room‐temperature solution‐processed ultrathin 2D MoS2 nanosheets are integrated into organic solar cells as an efficient hole extraction layer. An enhanced power conversion efficiency of 8.11% is achieved, which is superior to that of traditional vacuum‐evaporated molybdenum oxide. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>